2013
DOI: 10.1109/lgrs.2012.2196753
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Studies of Polarized Light Reflection From Sea Ice and Lake Ice in Visible and Near Infrared

Abstract: As the knowledge of polarized reflection from ice may be important for understanding radiative transfer in ice and be of potential value in imaging applications, spectral reflectances and linear polarization of sea ice and lake ice have been measured in visible and near infrared (NIR) (350-2500 nm) at nadir and the specular direction, respectively. Results are presented for three ice types: 1) black lake ice (bubble-free ice); 2) lake ice with air bubbles; and 3) sea ice with brine pockets but no air bubbles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Second, the upper layer of the sea ice melted and reformed, resulting in conditions less air bubbles in the sea ice. According to the research of SUN [ 32 ], less bubble ice has a lower reflectance. The reflectance of crude oil (area fraction 100%) is fairly constant below 1200 nm (the maximum value of reflectance is 0.02 and the minimum value is 0.009).…”
Section: Resultsmentioning
confidence: 99%
“…Second, the upper layer of the sea ice melted and reformed, resulting in conditions less air bubbles in the sea ice. According to the research of SUN [ 32 ], less bubble ice has a lower reflectance. The reflectance of crude oil (area fraction 100%) is fairly constant below 1200 nm (the maximum value of reflectance is 0.02 and the minimum value is 0.009).…”
Section: Resultsmentioning
confidence: 99%
“…Because of the limitations of our apparatus, 8° was the smallest phase‐angle measurement that we could obtain when rotating the arm in the viewing direction. NENULGS has been used to detect phase and spectral reflectance curves and the linear polarization degree of snow, soil, and ice when the incident light is unpolarized [ Lv and Sun , ; Sun et al , , ; Sun and Zhao , ; Sun et al , , ].…”
Section: Datamentioning
confidence: 99%
“…We found that the average absolute value of degree of linear polarization of the Spectralon measured by using our instrument was less than 0.01 in the range of 350 nm to 1000 nm; this value was represented as the polarimietric accuracy of our instrument. These parameters were appropriate for studying the polarization of natural surfaces [ Sun and Zhao , ; Sun et al , , ; Suomalainen et al , , ; Peltoniemi et al , ].…”
Section: Datamentioning
confidence: 99%
“…The NENULGS has been used to detect phase spectral curves of reflectance and degree of linear polarization of snow, soil and ice when the incident light is unpolarized [49][50][51]. A detailed description of the laboratory measurement system is given in [35].…”
Section: Measurements Instrumentsmentioning
confidence: 99%